High thermal stability of aliphatic polyurethanes prepared from sesame and peanut oil and their kinetic parameters - Desappan, Venkatesh; Viswanathan, Jaisankar (European Journal of Chemistry, 2018)
Thermo-responsive vegetable oil-based polyurethanes were successfully prepared by poly-condensation reaction in the mixture of polyol and hexamethylene diisocynate. The functionality and high molecular weight of the polyurethanes were characterized by Fourier Transform Infrared Spectroscopy (FTIR), Proton Nuclear Magnetic Resonance Spectroscopy (1H NMR), Carbon Nuclear Resonance Spectroscopy (13C NMR), and Gel Permeation Chromatography. The viscosity of the polyols was characterized by Rheometry and flow rate of the polyols were derived from power law model. The kinetic and thermodynamic parameters of synthesized polyurethanes HSCP and HPCP were calculated from by TG curve. Five different mass loss temperature was obtained in the TGA curve of HSCP and HPCP, which corresponded to the decomposition of the physically observed NH and C=O formed between polyol and diisocyanate, respectively. The average value of the activation energy calculated by Murray and White, Coats and Redfern, Doyle’s, and Freeman-Carroll’s method. The success of the investigated different vegetable oil-based polyurethanes, in comparison with the activation energy of the Freeman-Carroll’s method to determine the thermal stability and the lifetime prediction of the peanut and sesame oil-based polyurethanes is 1.87×105 and 1.27×104 s-1.